2019
DOI: 10.1128/aac.00144-19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Pharmacodynamics of a Novel Ceftibuten-Clavulanate Combination Antibiotic against Enterobacteriaceae

Abstract: A novel antibiotic combination of the oral cephalosporin ceftibuten (CTB) and the ␤-lactamase inhibitor clavulanate (CLA) is currently in development for urinary tract infections, including those caused by extended-spectrum-␤-lactamase (ESBL)-producing organisms. This study aimed to identify the pharmacodynamic index and magnitude of this index for CLA, when combined with a fixed CTB exposure (ϳ59% free time above the CTB-CLA MIC) against ESBL-producing Escherichia coli and Klebsiella pneumoniae (CTB-CLA MICs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It should be noted, however, that exposure requirements exceeding 100% fT > MIC in specific isolates were absent from the majority of these studies. While pharmacokinetic variability among mice in these studies can account for some of this variability, differences within individual isolates still contribute to varying pharmacodynamic thresholds, as demonstrated in in vitro chemostat experiments where drug exposure can be quantified in each individual model (Grupper et al, 2019). As a result, some have suggested that the variability in thresholds observed should be accounted for alongside pharmacokinetic variability and natural MIC variation when conducting Monte Carlo simulations to guide optimal dosing and susceptibility breakpoints (Soon et al, 2013).…”
Section: Summary Of Pharmacodynamic Thresholds From Pre-clinical Muri...mentioning
confidence: 99%
“…It should be noted, however, that exposure requirements exceeding 100% fT > MIC in specific isolates were absent from the majority of these studies. While pharmacokinetic variability among mice in these studies can account for some of this variability, differences within individual isolates still contribute to varying pharmacodynamic thresholds, as demonstrated in in vitro chemostat experiments where drug exposure can be quantified in each individual model (Grupper et al, 2019). As a result, some have suggested that the variability in thresholds observed should be accounted for alongside pharmacokinetic variability and natural MIC variation when conducting Monte Carlo simulations to guide optimal dosing and susceptibility breakpoints (Soon et al, 2013).…”
Section: Summary Of Pharmacodynamic Thresholds From Pre-clinical Muri...mentioning
confidence: 99%
“…In studies that explored different PK/PD indices for BLI, the fraction of the dosing interval that the free drug concentration is above a threshold concentration ( fT >CT ) was identified as the best PK/PD index for tazobactam, 50–53 , 57 avibactam 40 , 44 , 54 , 55 and clavulanic acid. 38 , 46 Consistent with this, Louie et al 47 demonstrated that fT >CT adequately describes the exposure–response relationship for avibactam. The PD portion of the PK/PD index of these BLIs, due to lack of intrinsic antibacterial activity, is usually represented by a C T for inhibition instead of MIC.…”
Section: Resultsmentioning
confidence: 75%
“…A total of 23 studies were included in this systematic review. 38–60 From these, 11 studies used in vitro infection models, 39 , 43 , 44 , 46–48 , 52 , 56–59 7 studies used in vivo infection models, 38 , 40 , 49–51 , 53 , 60 and 2 studies used both in vitro and in vivo infection models 45 , 54 to evaluate the optimal concentration of BLI necessary to protect the companion BL antibiotic. Three of the studies were based on in silico methods, using mathematical modelling to determine the outcome of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Ceftibuten-clavulanate was the most active oral agent tested against a world-wide collection of 5,568 isolates of Enterobacteriaceae from 2017 [146,147]. Moreover, the pharmacodynamics of ceftibuten-clavulanate were evaluated in an in vitro chemostat model and a murine thigh infection model using ESBL-producing Enterobacteriaceae [148,149]. Unfortunately, in April 2019, Achaogen filed for bankruptcy, so the future of ceftibutenclavulanate is unclear.…”
Section: Ceftibuten-clavulanatementioning
confidence: 99%